Abdominoplasty: A Proposal of Results by Measurement - Susanto, Imam (Jurnal Plastik Rekonstruksi, 2013)
Background: Among body contouring procedures, abdominoplasty is a procedure, which cosmetic surgery patients seek most frequently. The aim of abdominoplasty is to fulfill the ideal appearance of the abdomen without complication. Optimal results and proposed best accuracy measurement tool for abdominal dimension will be presented.Patients and Methods: Two female patients with abdomen type III and IV, underwent surgical correction with choice of total abdominolipectomy. Pre-operative and post-operative evaluations and photographs of patients were documented. Appearance of abdomen, quality of the scar, and navel were evaluated.Results: Total abdominolipectomy was performed in two cases of woman with abdomen type III and IV. All of the patients have shown abdominal dimension reduction and the result was good and satisfying. Author proposed a measurement including abdominal dimension in three different levels of circumference : midline point circumference between navel to xyphoid, navel level circumference, and anterior superior spina illiac level circumference, quality of scar, navel, and abdominal appearance, which are documented before surgery, three weeks after surgery and three months post surgery.Summary: Optimal outcome in abdominoplasty is determined not only by appropriate surgical technique, but also by the selection design, how the dissection is done, the excision, suturing technique, and post-surgical care treatment. Author proposed a measurement form evaluated by the surgeon, patient, and observer to collect more precise objective and subjective results.